Perceived Risk and Fashion on the Intention to Adopt Wireless Earbuds in the United States Using a Partial Least Squares-Structural Equation Modeling Approach: Empirical Study - Edward M Lee; Chandrasekar Subramaniam; Sungjune Park (JMIR Formative Research, 2025)
Abstract BackgroundThe number of studies on the use of smart wearables has increased dramatically in recent years. However, aspects including personal safety and fashion perspectives of wearable devices have not yet been adequately addressed in the literature. There have been debates regarding the potential health risks and fashionability of using wearable devices. Regardless of the actual impact of such devices, these aspects may influence users’ perceptions toward the purchase and use of wearable technology. ObjectiveThis paper addresses the following research question: How do perceptions of risk and fashion affect the user’s intention to purchase and use wireless earbuds? MethodsA survey was administered to assess perceptions on health and privacy risks, fashionability, and wearable comfort of wireless earbuds, alongside questions on behavioral intention regarding their purchase and use. All questions were adapted from prior research and measured using a 7-point Likert scale. The final sample of 205 responses was analyzed using the partial least squares method with Smart-PLS software. ResultsPerceived health risk (PPPP ConclusionsAs new types of emerging technology are introduced to the market, technology acceptance models should evolve to better understand consumers’ perceptions toward these new technologies, from both academic and practical points of view.